Interval Representations - Santiago, R.H.N.; Bedregal, B.R.C; Acióly, B.M. (Trends in Computational and Applied Mathematics, 2004)
This paper presents the concept of interval representation and shows some of its properties. The concept is often applied in interval mathematics and captures the essence of that theory; namely: Interval analysis is a language that designates computations with real numbers. The idea of interval objects as representation of real objects is defined and its relation with some aspects of interval analysis is showed. Some of these relations are concerned with the topological aspects of intervals (Scott topology).